ESTETIKA SUFISTIK DAN ESTETIKA TAUHIDIK: PERSPEKTIF FILOSOFIS KOMPARATIF - Muh Farkhan M (CMES (Center of Middle Eastern Studies), 2020)
This article discusses the concept of Islamic aesthetics, which is the view of art and beauty according to Ismail Raji Al Faruqi and Seyyed Hossein Nasr, the representation of the two intellectual figures is seen as representing a pattern of religious understanding, especially with regard to the perspective of art objects in Islam. The aim is to explain descriptively the comparative views of the two modern Islamic thinkers and examine how Muslims respond to their thoughts in the Islamic art world today. furthermore, the article explain conceptually how religious art thought is believed and chosen as a basis in determining the direction and expression of art in the socio-cultural space. The method used in this study is descriptive qualitative analytic, with a religious philosophical approach to Islam, while data collection techniques are carried out through literature that is described qualitatively. The results show that aesthetics built on Sufistic conception and spiritual appreciation so distinctively in it’s paradigm. The Sufistic paradigm emphasize how art is able to strengthen one's psyche without debating legal status, while monotheistic aesthetics built on the basis of the legal text and dogmatism emphasize the exoteric level as legally considered by Islamic Islamic law. Thus the social responsibility and the selection of aesthetic views are sectarian in accordance with their religious beliefs.